The association between experiential and material expenditures and subjective well-being: New evidence from Hungarian survey data - Tamás Hajdu; Gábor Hajdu (Hungarian Academy of Sciences, Institute of Economics, 2015)
In the last decade, a number of experiments have stated that spending money on experiences rather than on material goods tends to make people happier. However, the experimental designs used to analyze the relationship between consumption and subjective well-being had several limitations: small and homogeneous samples, a direct question assessing the effect of consumption, and a potential social desirability bias due to the stigmatization of materialism. To reduce these limitations, we used a survey method. In two studies based on survey data from nationally representative samples in Hungary, we estimated linear and non-linear associations of experiential and material expenditures with life satisfaction. Although both experiential and material expenditures were positively associated with life satisfaction, evidence supporting the greater return received when buying experiences was limited. The main difference between experiential purchases and material purchases was that the marginal utility of experiential purchases appeared to be linear, whereas the marginal utility of material purchases was decreasing. Despite the limited differences between the effects of experiential and material purchases, the results of the non-linear estimates indicate that to maximize life satisfaction, an average person should allocate more money to buying experiences rather than material goods.
Keywords: I31; D12; 330; subjective well-being; life satisfaction; consumption; experiential purchase; material purchase